Epigenetic modification in Parkinson’s disease - Song, Hao; Chen, Juanli; Huang, Jin; Sun, Peng; Liu, Yanming; Xu, Li; Wei, Chuanfei; Mu, Xin; Lu, Xianjie; Wang, Wei; Zhang, Nan; Shang, Miwei; et al. (Frontiers in Cell and Developmental Biology, 2023)
Parkinson’s disease (PD) is a common neurodegenerative disorder caused by genetic, epigenetic, and environmental factors. Recent advance in genomics and epigenetics have revealed epigenetic mechanisms in PD. These epigenetic modifications include DNA methylation, post-translational histone modifications, chromatin remodeling, and RNA-based mechanisms, which regulate cellular functions in almost all cells. Epigenetic alterations are involved in multiple aspects of neuronal development and neurodegeneration in PD. In this review, we discuss current understanding of the epigenetic mechanisms that regulate gene expression and neural degeneration and then highlight emerging epigenetic targets and diagnostic and therapeutic biomarkers for treating or preventing PD.